Coseismic slip distribution for the Mw 9 2011 Tohoku‐Oki earthquake derived from 3‐D FE modeling. Issue 7 (30th July 2013) - Kyriakopoulos, C.; Masterlark, T.; Stramondo, S.; Chini, M.; Bignami, C.
Abstract [1] The coseismic slip distribution of the Mw 9.0 2011 Tohoku‐Oki earthquake has been estimated by inverting near‐field onshore and offshore geodetic data, using Green's function calculated with a 3‐D finite element (FE) model. The FE model simulates several geophysical features of the subduction zone that hosted the rupture surface of the event. These features include a 3‐D geometric configuration and distribution of material properties of the tectonic system, a precise geometric configuration of the irregular rupture surface, and an irregular free surface according to the topography and bathymetry. A model that simulates rupture along the interface between the relatively weak overriding Okhotsk plate and stiff subducting slab of the Pacific Plate requires less slip to produce the observed surface deformation, compared to a model having uniform material properties across the rupture interface. Furthermore, the estimated slip of the heterogeneous model is more widely distributed over the shallow portion of the plate boundary, whereas the estimated slip of the homogeneous model is more focused updip of the epicenter. This demonstrates the sensitivity of inverse analyses of geodetic data for the 2011 Tohoku‐Oki earthquake to the simulated domain geometry and configuration of material properties.